The rhetoric of love in religious peacebuilding - Steen-Johnsen, Tale (Journal of contemporary religion, 2020)
Religious leaders involved in peacebuilding initiatives often refer to the religious value of love to encourage groups in conflict to live peacefully together. In this article, I suggest that references to love as a religious value might contribute to bridging social capital, meaning social bonds between groups who have experienced conflict. However, without simultaneously addressing questions of justice, which is often necessary in violent conflicts, creating social bonds through references to love constitutes a weak contribution to peace. The article uses the study of a religious peacebuilding project in Ethiopia as an example and illustrates how religious leaders failed to make a substantial contribution to peace by evoking love but avoiding questions of justice.